2010
DOI: 10.1016/j.juro.2010.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of OnabotulinumtoxinA for Idiopathic Overactive Bladder: A Double-Blind, Placebo Controlled, Randomized, Dose Ranging Trial

Abstract: OnabotulinumtoxinA at doses of 100 U or greater demonstrated durable efficacy in the management of idiopathic overactive bladder and urinary urgency incontinence. A dose of 100 U may be the dose that appropriately balances the symptom benefits with the post-void residual urine volume related safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
312
9
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(354 citation statements)
references
References 24 publications
26
312
9
7
Order By: Relevance
“…Unfortunately, in this study the amount of 200 U of onabotulinumtoxinA was twice as high as the registered and reimbursed dose for idiopathic OAB and not the standard of care for this third-line therapy. This alternative dose of 200 U was used off label before the compound was registered for idiopathic OAB, but this is not clinical practice at present due to higher chance of adverse events like urinary retention and urinary tract infection [34]. The registered dose of onabotulinumtoxinA for idiopathic OAB is 100 U, which was significantly more effective than placebo at 4 months [35].…”
Section: Oab With or Without Urinary Incontinencementioning
confidence: 99%
“…Unfortunately, in this study the amount of 200 U of onabotulinumtoxinA was twice as high as the registered and reimbursed dose for idiopathic OAB and not the standard of care for this third-line therapy. This alternative dose of 200 U was used off label before the compound was registered for idiopathic OAB, but this is not clinical practice at present due to higher chance of adverse events like urinary retention and urinary tract infection [34]. The registered dose of onabotulinumtoxinA for idiopathic OAB is 100 U, which was significantly more effective than placebo at 4 months [35].…”
Section: Oab With or Without Urinary Incontinencementioning
confidence: 99%
“…With this dose the response rate (in the reports usually defined as >50% improvement or 'improved' or 'greatly improved' on Treatment Benefit Scales) is in excess of 60% in most studies (range 37-70%), typically with a 20-50% reduction in incontinence episodes (i.e. about 3 fewer leaks per 24 hours), 23-55% of patients achieving continence, and statistically significant improvement in quality of life measures [2][3][4][6][7][8] (Table 3). The response rate in our study is somewhat lower at 43% at one month and 36% at three months, and while there was statistically significant reduction in incontinence episodes (p=0.01) and leakage (p=0.025), the numbers are lower than those reported after cystoscopic injection.…”
Section: Comparison With Cystoscopic Injectionmentioning
confidence: 99%
“…2-3 fewer leaks per 24 hours), 23-55% of patients achieving continence, and a statistically significant improvement in quality of life measures [2][3][4][6][7][8] . The main complications are a 5-36% risk of UTI [2][3][4][5][6]9] and a 4-11% risk of impaired bladder emptying requiring catheterization [1,3,4,6,9] . Some patients also experience postoperative pain and dysuria.…”
Section: Introductionmentioning
confidence: 97%
“…20 Large randomised trials have shown efficacy in men and women with OAB with or without detrusor overactivity (DO), as well as those with neurogenic DO. 21,22 A good response appears achievable in approximately 85 per cent of patients. The treatment is typically performed as an outpatient procedure under local anaesthetic.…”
Section: Botulinum Toxin-amentioning
confidence: 99%